A novel probe‐fed directional dielectric resonator antenna for mobile communication. Issue 4 (11th November 2022) - Luo, Wei; Jiang, Lanlan; Yi, Ren
Abstract: A directional dielectric resonator antenna (DDRA) for 5G mobile communication system is proposed. The antenna is side‐fed with the metal probe to make it work in quasi‐TEδ11 mode, so as to realize the characteristics of directional radiation. The stacked structure is adopted, and the two side walls of the rectangular dielectric resonator parallel to the microstrip line are grooved to improve the frequency bandwidth of the antenna. Furtherly, the Koch snowflake fractal is used for the second iteration of the top cylindrical dielectric resonator, and the parasitic metal columns inside the DRA are also helpful for the enhancement of bandwidth. The prototype was fabricated and tested to verify the design, and the measured results show −10 dB impedance bandwidth of about 23% and an average gain of 5.2 dBi within the operation band.